Comparison of amino acids profile and antioxidant activities between edible bird nest and chicken egg - Ahlam Abdaslam M Ali,; Hidayati Syamimi Mohd Noor,; Chong, Poh Kei; Abdul Salam Babji,; Lim, Seng Joe (Penerbit Universiti Kebangsaan Malaysia, 2019)
Edible bird’s nest (EBN) and eggs are sources of high quality protein. The objectives of this study were to compare the amino acid profile between EBN and eggs to determine the differences in nutrition composition and antioxidant properties. Amino acid profile and antioxidant properties (DPPH, ABTS and FRAP) of four samples, raw EBN (EBNraw), EBN hydrolysates (EBNh), commercial chicken egg (Eggcomm) and free range chicken egg (EggFR) were determined and correlated with one another. It was found that EBN raw and EBNh have significantly higher (p<0.05) DPPH and ABTS activities compared to Eggcomm and EggFR, whereas Eggcomm and EggFR have significantly higher (p<0.05) FRAP activities compared to EBNraw and EBNh. Amino acid profile analysis showed that Eggcomm and EggFR have significantly higher (p<0.05) methionine, cysteine, lysine and isoleucine content compared to EBNraw and EBNh. Histidine, proline, phenylalanine and tryptophan in EBN were found to have significant (p<0.01) positive correlation with DPPH and ABTS antioxidant activities assays, while methionine and cysteine in chicken eggs have significant (p<0.01) positive correlation with FRAP activity. In conclusion, both EBN and chicken eggs are good sources of proteins and essential amino acids, but EBN showed higher antioxidant activities.